Physicians and Iatrogenism from the Philosophy of Medicine to the Sociology of Health - Can, İslam (My University, 2024)
In pre-modern times, health services provided by traditional healers such as clergymen, healers, and herbalists were conducted by professionalss specialized in modern medicine such as physicians and auxiliary health personnel. Although modern Western medicine has developed in many areas, it has been criticized severely. The most important of these criticisms is the unquestionable structure of modern medicine and the methods and techniques used by physicians in the treatment processes in connection with this structure. These criticisms are termed with the concept of iatrogenesis, and criticisms against both modern medicine and physicians are becoming sharper. In this study, the forms of iatrogenesis produced by modern medicine in general and by physicians in particular will be discussed from the perspective of medical philosophy and health sociology. In addition, the relationship between physicians and iatrogenism will be evaluated in the context of recently discussed issues such as patient-physician relations, commercialization of health services, construction of the patient as a customer, pharmaceutical industry and guided scientific studies, excessive use of drugs and medical devices, medicalization of life, gaining popularity of traditional treatment methods.
Keywords: Iatrogenesis; Health sociology; Philosophy of medicine; The profession of medicine; Modern medicine.